2022
DOI: 10.3390/molecules27196533
|View full text |Cite
|
Sign up to set email alerts
|

Amauroderma rugosum Extract Suppresses Inflammatory Responses in Tumor Necrosis Factor Alpha/Interferon Gamma-Induced HaCaT Keratinocytes

Abstract: Keratinocytes form the physical barrier of the skin and play an important role in the inflammatory process. Amauroderma rugosum is an edible mushroom; however, its pharmacological properties have seldom been studied. Although the anti-inflammatory effect of the organic solvent extract of Amauroderma rugosum has been previously reported, it is not known whether the aqueous extract has a similar effect. In addition, the effect of Amauorderma rugosum extract on skin has never been explored. Therefore, the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…To determine the active ingredient responsible for the antioxidant effects of ARW, DPPH assays were performed on the chemical components of ARW, as described in a previous study [ 8 ]. Of the components examined, only gallic acid demonstrated a scavenging effect on the DPPH• free radicals, with an SC 50 value of 7.429 µM.).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the active ingredient responsible for the antioxidant effects of ARW, DPPH assays were performed on the chemical components of ARW, as described in a previous study [ 8 ]. Of the components examined, only gallic acid demonstrated a scavenging effect on the DPPH• free radicals, with an SC 50 value of 7.429 µM.).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of AR was determined using analytical methods, indicating the presence of sterols, flavonoids, fatty acids, esters, aromatic acids, esters, phenols, polysaccharides, and triterpenes [ 15 ]. An earlier investigation conducted using liquid chromatography-mass spectrometry (LC-MS) showed that ARW contains several major compounds, namely, ganoderic acid A, ganoderic acid D, ganoderic acid J, oleamide, (9Z, 12Z)-octadeca-9,12-dienamide, uridine, guanosine, cytosine, uracil, adenosine, adenine, gallic acid, dextrose, and l -arabinopyranose [ 8 ]. The administration of oleamide effectively mitigated the detrimental effects of 3-NP on mitochondrial function and cell survival in rat cortical sections.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study conducted by Chan et al confirmed AR’s ability to scavenge DPPH and ABTS radicals in the LPS-treated murine macrophage RAW264.7 cells [ 254 ]. Meanwhile, Shiu et al demonstrated that AR reduced intracellular ROS levels and inhibited the release of oxidant-stress-related cytokines and chemokines like IL-1β and IL-8 in TNF-α- and IFN-γ-stimulated HaCaT keratinocytes [ 257 ]. The study also identified that AR can downregulate key signalling pathways related to oxidant stress, including NF-κB, MEK1/2, ERK1/2, and Akt/mTOR.…”
Section: Evaluating the Potential Of Bioactive Supplements And Herbs ...mentioning
confidence: 99%
“…Sanguinoderma species have been found to contain a large number of secondary metabolites, such as polysaccharides, sterols and unsaturated fatty acids, that are extremely effective against tumor progression ( Shiu et al . 2022 ), cardiovascular disease ( Li et al .…”
Section: Introductionmentioning
confidence: 99%